Resveratrol Improves Growth Performance, Intestinal Morphology, and Microbiota Composition and Metabolism in Mice - Zhuang, Yu; Huang, Huijun; Liu, Shuang; Liu, Feng; Tu, Qiang; Yin, Yulong; He, Shanping (Frontiers in Microbiology, 2021)
Background Resveratrol (RSV) plays a vital role in alleviating various stresses and improving intestinal health. The current study was conducted to explore whether RSV alleviates weaning stress through improving gut health in a weaning mouse model. Forty 21-day-old weaned mice were randomly assigned to a control group without RSV treatment and three treatment groups with 10, 20, and 50 mg/kg RSV for 28 days. Results The results showed that RSV at a dose of 20 mg/kg improved total body weight, intestinal morphology (villus length and the ratio of villus length to crypt depth), and the levels of intestinal barrier proteins (claudin-1 and occludin), but had little effect on the food intake, crypt depth, and serum free amino acids of mice. Compared with the control group, mice supplemented with RSV had decreased mRNA expression of genes related to inflammatory cytokines (IL-6 and IL-1β), but increased mRNA expression of genes related to host defense peptides (Defa3, Defa5, Defa20, and Lyz) and short-chain fatty acids (SCFAs) production (propionic acid, isobutyric acid, butyric acid, and isovaleric acid). In addition, 16S rRNA sequencing results showed that RSV supplementation increased the richness indices of intestinal microbiota (Chao, ACE) and shaped the composition of intestinal microbiota (e.g., increased β-diversity of intestinal microbiota community). Meanwhile, RSV supplementation increased genes of Butyricicoccus, Ruminococcus_1, and Roseburia, which are producers of SCFAs. Furthermore, RSV supplementation significantly influenced the metabolism of intestinal microbiota, namely, amino acids metabolism, lipid metabolism, and defense mechanisms. Conclusion RSV can improve growth performance and intestinal morphology in weaning mice, possibly through improving gut immune response and microbiota function.